Salt-Sensitive Hypertension of the Renal Tubular Cell–Specific NFAT5 (Nuclear Factor of Activated T-Cells 5) Knockout Mice. Issue 5 (November 2021) - Hiramatsu, Akiko; Izumi, Yuichiro; Eguchi, Koji; Matsuo, Naomi; Deng, Qinyuan; Inoue, Hideki; Nakayama, Yushi; Nonoguchi, Hiroshi; Aramburu, Jose; López-Rodríguez, Cristina; Kakizoe, Yutaka; Adachi, Masataka; et al.
Abstract : The kidney plays a crucial role in blood pressure (BP) regulation by controlling sodium reabsorption along the nephron. NFAT5 (nuclear factor of activated T-cells 5) is a transcription factor that is expressed in various tissues including the kidney and is activated at hypertonic conditions as observed in the renal medulla; the role for kidney NFAT5 in BP regulation, however, remains still obscure. In the present study, we generated inducible and renal tubular cell–specific NFAT5 knockout (KO) mice and characterized their phenotype. The NFAT5 KO mice exhibited high BP, hypernatremia, polyuria, and low urinary sodium excretion without significant alterations in the plasma renin activity or aldosterone concentration. The mice fed a high-salt diet further increased BP, revealing salt-sensitive hypertension. The KO mice exhibited the increased gene expression of the epithelial sodium channel. Protein expression of epithelial sodium channel in the membrane fraction was also significantly increased in KO mice than in wild-type mice. Treatment with amiloride, an epithelial sodium channel blocker, corrected high BP, hypernatremia, and decreased urinary sodium excretion in KO mice to the same levels of those in wild-type mice. Finally, the effects of high-salt diet and amiloride in KO mice were confirmed by the radiotelemetry method. In conclusion, these data indicate that renal tubular NFAT5 should play an important role in regulating sodium reabsorption through epithelial sodium channel under high-salt conditions, thereby preventing salt-dependent hypertension. Abstract : Supplemental Digital Content is available in the text.